Advances in Big Data and Cloud Computing Proceedings of ICBDCC18 - Peter, J. Dinesh; Alavi, Amir H.; Javadi, Bahman; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
This book is a compendium of the proceedings of the International Conference on Big Data and Cloud Computing. It includes recent advances in the areas of big data analytics, cloud computing, internet of nano things, cloud security, data analytics in the cloud, smart cities and grids, etc. This volume primarily focuses on the application of the knowledge that promotes ideas for solving the problems of the society through cutting-edge technologies. The articles featured in this proceeding provide novel ideas that contribute to the growth of world class research and development. As this book is a concise compilation of articles approved by the panel of expert reviewers, the contents of this proceeding will prove to be an invaluable asset to the researchers in the area of advanced engineering sciences.
Chapter 1: Big-Data -- Chapter 2: Cloud Computing -- Chapter 3: Cloud Security -- Chapter 4: Data Analytics in Cloud -- Chapter 5: Big-Data and Cloud Computing Applications.
Keywords: Computational intelligence; Big data; Telecommunication; Computational Intelligence; Big Data; Communications Engineering, Networks